2007
DOI: 10.1007/s10490-007-9068-x
|View full text |Cite
|
Sign up to set email alerts
|

The turtle–hare race story revisited: Social capital and resource accumulation for firms from emerging economies

Abstract: Emerging economies, Social capital, Relational embeddedness, Structural embeddedness, Resource accumulation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 118 publications
0
23
0
Order By: Relevance
“…Ferrier et al (1999) discussed that the number and speed of competitive actions help market leaders defend their positions against challengers. As such, the old-line MNE is likely to lose the game if it takes a hubristic "hare nap," while the emerging MNE competes more persistently and vigorously (Li, Lin, & Arya 2008b). Resting on its competitive advantages will inevitably make the old-line MNE vulnerable to the competitive actions of the emerging MNE, which unleashes locally sensitive strategies and neutralizes the competitive advantages of the old-line MNE (Chang & Park, 2012;Dawar & Frost, 1999).…”
Section: Propositionmentioning
confidence: 99%
“…Ferrier et al (1999) discussed that the number and speed of competitive actions help market leaders defend their positions against challengers. As such, the old-line MNE is likely to lose the game if it takes a hubristic "hare nap," while the emerging MNE competes more persistently and vigorously (Li, Lin, & Arya 2008b). Resting on its competitive advantages will inevitably make the old-line MNE vulnerable to the competitive actions of the emerging MNE, which unleashes locally sensitive strategies and neutralizes the competitive advantages of the old-line MNE (Chang & Park, 2012;Dawar & Frost, 1999).…”
Section: Propositionmentioning
confidence: 99%
“…Social capital is a valuable asset for firms to help manage interfirm relationships and it impacts on the quality of cooperation and resource access (Li et al, 2008). According to Walker et al, (1997: 3 An illustration of the connected caveman graph (Watts, 1999b).…”
Section: Theoretical Basesmentioning
confidence: 99%
“…These two dimensions have been widely adopted in other studies and shown to be highly interrelated instead of mutually exclusive (e.g., Li, Lin, & Arya, 2007;Liao & Welsch, 2005;Tsai & Ghoshal, 1998;Zukin & DiMaggio, 1990). Each of these two dimensions facilitates flows of knowledge and enables entrepreneurs to discover opportunities when facing poor information communications.…”
Section: Social Capitalmentioning
confidence: 99%